“No Patient” : Early HIV/AIDS epidemic in Korea and Government Response - Junho JUNG (Uisahak)
HIV/AIDS control in Korea characterized with “AIDS Prevention Law”, enacted in 1987. It was one of the first separate legal enforcement around the world that governs control of the HIV/AIDS epidemic. Yet with significant limitations regarding human rights, as it criminalized HIV infection, and dictates penal action against ‘transmitters’. This papers looks into how HIV/AIDS epidemic started in Korea in 1980s, with specific focus on disease narrative that was constructed by the government. It was known to United States Forces Korea, that HIV was already spreading steady into Korean female sex workers around U.S. military bases in 1985. This information was concealed by Korean Ministry of health, in the face of upcoming international events such as 1988 Seoul Olympics. Instead, the Korean government turned public attention to ‘imported’ cases, constructing narrative that HIV/AIDS as a foreign disease. With direction of president, HIV/AIDS control focus on compulsory testing and isolation of identified risk group of sexual minorities and sex workers around U.S. military bases. This narrative of foreign disease had lasting impact even after democratization of Korea in 1987, as civil society, unaware that HIV/AIDS had already became endemic in Korea, argued to enforced compulsory testing against foreign nationals upon entry. This paper argues that disease narratives were carefully constructed by the government during early phase of HIV/AIDS epidemic in Korea, and used legal structure as ways to conceal the actual prevalence from both domestic and international attention.